Diffusible Tumor Necrosis Factor-Alpha (TNF-α) Promotes Noise-Induced Parvalbumin-Positive (PV+) Neuron Loss and Auditory Processing Impairments - Deng, Di; Wang, Weihua; Bao, Shaowen (Frontiers in Neuroscience, 2020)
Neuroinflammation has been implicated in noise-induced auditory processing deficit and tinnitus. Certain nonauditory neurological disorders can also increase the levels of proinflammatory cytokines in the brain. To investigate the impact of increased brain proinflammatory cytokine levels on the central auditory pathway, we infused recombinant TNF-α into the right lateral cerebral ventricle, and examined auditory processing and cytoarchitecture of the auditory cortex. Microglial deramification was observed in the auditory cortex of mice that had received both TNF-α infusion and exposure to 86-dB noises, but not in mice that had received either TNF-α infusion or noise exposure alone. The observed microglial deramification was correlated with reduced cortical PV+ neuron density and impaired performances in gap detection and prepulse inhibition (PPI). These results suggest that disease-related increase in brain proinflammatory cytokine release could be a risk factor for noise-induced auditory processing deficits and tinnitus.